2018
DOI: 10.1021/acs.jnatprod.8b00343
|View full text |Cite
|
Sign up to set email alerts
|

Macrophilones from the Marine Hydroid Macrorhynchia philippina Can Inhibit ERK Cascade Signaling

Abstract: Six new macrophilone-type pyrroloiminoquines were isolated and identified from an extract of the marine hydroid Macrorhynchia philippina. The proton-deficient and heteroatom-rich structures of macrophilones B-G (2-7) were elucidated by spectroscopic analysis and comparison of their data with those of the previously reported metabolite macrophilone A (1). Compounds 1-7 are the first pyrroloiminoquines to be reported from a hydroid. The macrophilones were shown to inhibit the enzymatic conjugation of SUMO to pep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Oxidation by Fremy's salt yielded the iminoquinone, which, after the introduction of the thioether group by sodium methanethiolate, furnished the natural product 423 in just 4% yield over three steps (Scheme 26) [325]. Once more, the group of Gustafson and co-workers published the isolation of six further macrophilones B-G (424-429) from the same source one year later (Figure 59) [326]. Just as its related congener macrophilone A (423), compounds 424-429 showed moderate to weak inhibition effects of SUMO conjugation cascade (IC50 values ranging between 11.9 µM and >100 µM).…”
Section: Pyrroloiminoquinone and Related Analogsmentioning
confidence: 99%
See 2 more Smart Citations
“…Oxidation by Fremy's salt yielded the iminoquinone, which, after the introduction of the thioether group by sodium methanethiolate, furnished the natural product 423 in just 4% yield over three steps (Scheme 26) [325]. Once more, the group of Gustafson and co-workers published the isolation of six further macrophilones B-G (424-429) from the same source one year later (Figure 59) [326]. Just as its related congener macrophilone A (423), compounds 424-429 showed moderate to weak inhibition effects of SUMO conjugation cascade (IC50 values ranging between 11.9 µM and >100 µM).…”
Section: Pyrroloiminoquinone and Related Analogsmentioning
confidence: 99%
“…Just as its related congener macrophilone A (423), compounds 424-429 showed moderate to weak inhibition effects of SUMO conjugation cascade (IC50 values ranging between 11.9 µM and >100 µM). Furthermore, they exhibited significant toxicity against several cancer cell lines (no values given) [326]. To investigate their bioactivity potential, the first isolation of macrophilone A (423) was accompanied by its synthesis [325].…”
Section: Pyrroloiminoquinone and Related Analogsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zlotkowski et al [ 37 ] showed that Macrophilone A increased intracellular reactive oxygen species levels and caused cytotoxicity in lung adenocarcinoma cells. Further studies showed that other Macrophilones caused cytotoxicity as well [ 38 ]. Lytophilippines were able to induce antibacterial, antiviral, and antitumor activities, besides displaying lethality in shrimps [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The stinging hydroid is widely distributed and sometimes considered invasive . However, its natural product chemistry has been only sparsely investigated …”
mentioning
confidence: 99%